A Theoretical Synthesis of Job Performance and the Evaluative Dimension of Organizational Climate: A Social Psychological Perspective - Meglino, Bruce M. (Academy of Management Review, 1976)
Studies linking organizational climate to job performance have been diverse and at times contradictory; however, social psychologists have dealt with a similar problem in the area of social facilitation. Social facilitation is related to the evaluative aspect of organizational climate in an effort to explain previous contradictory results.